Objective liability for removal of trees or shrubs without the required permit in the light of recent judicature views - Czech, Marta (Polish Yearbook of Environmental Law, 2014)
The provisions of the Act on Nature Conservation treat the removal of trees and shrubs without the required permit as an administrative tort sanctioned by an administrative fine in the amount of a triple fee paid for the removal with the permit of the competent authority. This is the objective liability to which not the guilt but only the fact of removal of a tree (shrub), and the lack of the permit are significant. The administrative fine is imposed automatically, without considering the individual circumstances of the particular case. No possibilities to omit to impose the fine, such as state of necessity, or to adjust its amount are taken into account. In the general opinion this is excessive restriction of ownership right and the imposed sanction is seen as disproportionate in relation to the infringed good, as the amount of fines is considerable. This state of affairs makes the cases of removal of trees and shrubs frequently heard by the courts. On 1 July 2014 the Constitutional Court declared that article 88 section 1 point 2, and article 89 section 1 of the Act on Nature Conservation were inconsistent with article 64 section 1 and 3 in relation to article 31 section 3 of the Constitution.